(untitled) (Al-Farooq Journal of Sciences, 2026)
The measures implemented to fortify Libyan national identity 17 the February 2011 Revolution are examined in this paper, with particular attention paid to methods for acknowledging the nation’s ethnic and tribal diversity, which is a distinguishing characteristic of Libyan society. In order to prevent the exclusion or marginalization of any social components, it tackles the issue of how the state can simultaneously respect ethnic and tribal particularities and promote an inclusive national identity. Within the framework of Libya’s post-revolutionary political and social changes, the paper examines the potential and difficulties related to this undertaking. It also strives to reinforce national identity and foster a spirit of tolerance and coexistence among the nation’s many social groupings by offering a thorough perspective and useful policy proposals in the areas of education, culture, and the media.